Reviving traditional agricultural systems through pollinating insects - Duara, Pollobi (Journal of Advanced Education and Sciences, 2026)
Traditional agricultural systems rely heavily on ecological processes such as pollination, but not much study have been done in this field. The traditional agriculture system and the farmers associated with them lack knowledge about the role of pollinating insects in agriculture. This study aims to study the pollinating insect diversity and their role in traditional agroecosystems. Methods used were Field surveys, floral resource assessments, pollinator visitation studies and interviewing with the farmers. The study highlights the importance of community-based ecological management for sustainable agriculture. This study investigates the relationship between pollinating insects and traditional agroecosystems. Traditional systems with mixed crops and native flowering plants harbours higher pollinating insects compared to monocultures. Visitation rates were high in natural habitat where less chemicals were applied. Declines in pollinator activity was recorded in areas with more chemical use or limited flower diversity. Protecting pollinating insects not only benefits crop yields but also supports biodiversity. Pollination maintains crop diversity and also ensure food safety and security.